MAPPING THE INTERDISCIPLINARY LANDSCAPE OF DIGITAL ROMANTIC FRAUDS USING VOS VIEWER - Ronal Kamim; Arum Karisma Nadya Lakshita; Dwi Permana Putra; Hendro Margono (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2025)
Romance fraud is a crime committed through emotional manipulation via digital platforms, causing significant financial and psychological harm to victims. Despite growing prevalence, the phenomenon lacks unified terminology, with terms such as "love scam," "catfishing," and "sweetheart swindle" reflecting its conceptual complexity. This bibliometric analysis of 152 publications (2010?2025) maps the interdisciplinary landscape of online romance fraud research using Scopus data and VOSviewer software. Five critical findings emerge: (1) publication acceleration of 553 percent from 2020?2024, signaling urgent recognition as a sociotechnical crisis; (2) geographic imbalance with the United States, United Kingdom, and Australia accounting for approximately 70 percent of publications while Global South nations remain epistemically marginalized; (3) disciplinary shift from early technical cybersecurity framings toward holistic, trauma-informed perspectives emphasizing mental health and victimization; (4) methodological limitations with 85 percent employing descriptive statistics and lacking longitudinal victim tracking; and (5) authorship concentration wherein two scholars account for 21 percent of publications. Analysis identified five distinct thematic clusters cybercrime systems, victimology, psychological manipulation, platform-specific risks, and digital risk behavior demonstrating that romance fraud demands integrated frameworks bridging criminology, psychology, computer science, and public health. The research landscape is simultaneously accelerating, shifting toward psychosocial concerns, geographically concentrated in privileged nations, and methodologically conservative, creating urgent gaps in Global South perspectives, culturally-specific victim experiences, and longitudinal designs. These findings inform evidence-based prevention strategies, cross-sector policy interventions, victim support services, and open urgent opportunities for future multidisciplinary exploration, particularly Global South-led investigations and perpetrator-focused inquiry essential for developing effective intervention approaches.